Drinking water nanofiltration with concentrate foam fractionation—A novel approach for removal of per- and polyfluoroalkyl substances (PFAS). (1st April 2023) - McCleaf, Philip; Stefansson, William; Ahrens, Lutz
Highlights: PFAS was reduced to below 2 ngL −1 using NF for contaminated groundwater feedwater. PFAS removal efficiency was size selective for both the NF and concentrate's FF process. Long-chain PFAS was efficiently removed using air alone in concentrate FF. Shorter chain PFAS removal improved with cationic surfactant in concentrate FF. FF foam from concentrate treatment had 41 times higher PFAS concentration than NF feedwater and 2% of feedwater volume. Abstract: Per- and polyfluoroalkyl substances (PFAS) are recognized as persistent pollutants that have been found in drinking water sources on a global scale. Semi-permeable membrane treatment processes such as reverse osmosis and nanofiltration (NF) have been shown effective at removing PFAS, however, disposal of PFAS laden concentrate is problematic. Without treatment of the concentrate, PFAS is released into the environment. The present work examined a novel PFAS removal scheme for drinking water using NF filtration with treatment of the resulting NF concentrate via foam fractionation (FF) with and without co-surfactants. The NF-pilot removed 98% of PFAS from AFFF contaminated groundwater producing permeate with 1.4 ng L −1 total PFAS. Using FF resulted in ∑PFAS removal efficiency of 90% from the NF concentrate and with improved removal of 94% with addition of cationic co-surfactant. The resulting foamate composed approximately 2% of the NF feedwater volume and contained greater than 3000 ng L −1 PFAS or 41 times greater than the NF feedwater. Addition of the cationic co-surfactant to the FF process resulted in increased removal efficiency of the shorter chain PFAS, specifically 37% for PFPeA, 9% for PFHxA, and 34% for PFBS thus attaining 59%, 99% and 96% removal efficiency, respectively. PFOA, PFPeS, PFHxS, PFOS each attained 99% FF removal with or without co-surfactant addition. Graphical abstract: Image, graphical abstract